Late (5-20 Years) Outcome after STA-MCA Anastomosis and Encephalo-Duro-Myo-Arterio-Pericranial Synangiosis (EDMAPS) in Patients with Moyamoya Disease. (16th November 2020) - Kuroda, Satoshi
Abstract: INTRODUCTION: Surgical revascularization is known to reduce the incidence of further ischemic and hemorrhagic events in patients with moyamoya disease, but majority of previous studies reported their short-term (<5 years) outcome. METHODS: Cumulative incidence of late morbidity/mortality and disease progression were evaluated among 93 patients who underwent STA-MCA anastomosis and EDMAPS. All of them were prospectively followed up for longer than 5 years post-surgery (mean, 10.5 ± 4.4 years). There were 35 pediatric and 58 adult patients. Initial presentation included TIA/ischemic stroke in 80 patients, hemorrhagic stroke in 10, and asymptomatic in 3. Surgery was performed onto their 141 hemispheres. Follow-up MRI/MRA was performed with an interval of 6 or 12 months during follow-up periods. RESULTS: During follow-up periods, 92/93 patients were free from any stroke or death, but one recurred hemorrhagic stroke (0.10% per patient-year). Disease progression occurred in the territory of the contralateral carotid or posterior cerebral artery (PCA) in 19 hemispheres of 15 patients (1.5% per patient-year). The interval between initial surgery and disease progression very widely differed from 0.5 to 15 years. Repeat bypass surgery for anterior and posterior circulations resolved ischemic attacks in all 10 patients. CONCLUSION: STA-MCA anastomosis and EDMAPS would be the best choice to prevent further ischemic and hemorrhagic stroke for longer than 10 years through widely improving cerebral hemodynamics to both the MCA and ACA territories. However, regular follow-up would be essential for longer than 10 years post-surgery not to miss the disease progression in the territory of contralateral carotid artery and PCA and prevent late cerebrovascular events.